Innovative solar powered milk cooling system - CGIAR Research Program on Livestock (2017)
To reduce milk loss, a solar-powered milk cooling system was developed to refrigerate and store milk on the farm and cool it during transportation. Since 2015, the system has been undergoing tests in two projects in Tunisia and Kenya.